Why Did the Ruble Collapse in August 1998? - Desai, Padma (American Economic Review, 2000)
The factors that led to the collapse of the ruble are analyzed. It is argued that it resulted from exogenous factors (closely related to the unanticipated Asian financial crisis) interacting with inherited weaknesses in fundamentals (of fiscal policy) that made the Russian economy, while progressively being brought to macroeconomic stability, nonetheless vulnerable to a large external shock. It is contended that, instead of the policy mistake of August 1998 requiring a default of domestic debt and moratorium on payment of foreign commercial debt, a decision by Russian authorities to offer temporary exchange controls, sanctioned by the IMF and the U.S. Treasury as an emergency measure, would have been a better alternative, obviating the de facto partial and unilateral resort to controls that the moratorium and default implied.